Can cashew value chain industry improve food security: an empirical study from the Gambia - Bojang, Baseedy; Emang, Diana (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Food security is the most critical issue to address in The Gambia, and cashew production and its respective value chain provide opportunities to improve the quality of livelihood for many families. This study conducts value chain and SWOT analyses to provide information that could improve development opportunities and strengthen linkages to food security within the cashew industry in The Gambia’s Kombo East district, West Coast region. The results show that the cashew value chain in the study site is characterized by a large number of producers and relatively few intermediaries working through five marketing channels. The results demonstrate that farmers received 66% of the final market value, but there is a lack of farmer organizations, which severely affected farmers’ free and fair access to markets to sell their products. So, there is an immediate need to establish farmers’ cooperatives to reduce intermediaries in the value chain and obtain fair product prices. Moreover, the result of SWOT analysis revealed that the strategic position of the cashew industry is an advantageous ‘holds and maintains’ position, indicating a market penetration, product development, or modifying existing products, and a vertical integration strategy could increase revenue, alleviate poverty, and reduce food insecurity. Adopting the recommended market-based approaches will result in higher producer prices and incomes, thereby reducing poverty and food insecurity. The study contributes to the literature by focusing on the cashew chain value in The Gambia, added value opportunities through transformation, better markets, improved products, and other alternatives to promote global value creation, and the dynamics of the food system, which can promote food security and sustainable rural development.